Analysis of vocational education curriculum in ASEAN Economic Community: a literature review - Zulaikha Fitriyanti Zulaikha; Hasan Hariri; Riswanti Rini; Sowiyah Sowiyah (Goodwood Publishing, 2021)
Purpose: In 2015, ASEAN economic community was formed to turn the area into a single market and a competitive superior production base to make the region prosperous and stable. The how to do that is through education and applying the appropriate curriculum for industry's needs. This study analyzed and elaborated the curriculum used in vocational schools, especially in countries around ASEAN Economic Community or AEC. Research methodology: This descriptive content analysis study method was done by implementing a literature review. This literature review was to review and analyze the curriculum used in vocational education around AEC in order to fulfill the standards of AEC industry's needs. Results: This study finds that curriculum for vocational schools around ASEAN Economic Community set priority in standard skills and soft skills. Limitations: This study is limited to vocational schools, especially around ASEAN Economic Community. Contribution: This study could be useful for vocational schools around South East Asia and researchers researching curriculum, especially in Asia. Keywords: AEC, Curriculum, Vocational education